A contribuição dos jogos de papéis sociais no desenvolvimento psíquico da criança na idade pré-escolar: elementos da teoria histórico-cultural - Alves, Vitória Ferreira (Universidade Federal do Tocantins, 2025)
This study aimed to analyze the importance of social role-playing games, as a playful activity, in the process of developing higher psychological functions in children aged 4 to 5 years. As a way of discussing the topic, we discussed the process of human development, from a historical-cultural perspective, demonstrating that social and cultural relationships are responsible for the development of higher psychological functions in social beings. Furthermore, we addressed the importance of playful activities for the cognitive development of children, emphasizing that they play a fundamental role in the construction of social relationships and that they contribute to the insertion of children in the material and symbolic life of human productions; and that the appropriation of the real world by infants occurs via objects and social meanings. Thus, we discussed the relevance of social role-playing games in the psychological development of children aged 4 to 5 years, and the importance that this playful activity has for this process and for the construction of the child's personality. The methodology used in this study is based on exploratory bibliographic research, a literature review, with a qualitative approach supported by books, specialized magazines, and scientific articles relevant to the topic. In short, in an engaging and intentional learning environment, children will be able to experiment, create, and imagine, since the game of social roles involves more elaborate and complex mental processes. Based on the studies carried out, which make up this final course work, we found that encouraging these playful practices in the educational context is crucial for the healthy psychological development of children, contributing significantly to the formation of more conscious, creative, and socially integrated individuals. Playfulness, by assuming a central role in the educational process, becomes an indispensable tool for the integral growth of the child.